Appropriation of biodiversity and traditional knowledge: a case study of two rural communities in Rio de Janeiro state, Brazil. - Boscolo, Odara Horta; Fernandes, Lucia (Scientia Plena, 2014)
Brazil is the largest holder of biological diversity in the world and has also a significant number of local communities and indigenous people who hold great knowledge of their habitats. This study aimed to identify the potential of commercial rights appropriation of native Brazilian plants raised in a ethnobotany research in two communities in the mountainous region of the state of Rio de Janeiro by searching patent databases. The monitoring of patent documents allows the search of several kinds of information, including indicators of technological researches of countries.This research was conducted using native plants cited by communities during 2009 and 2010, for its scientific and common names. This search was carried out in the documents of the following offices: European Patent Office, Japan Patent Information Organization, States Patent and Trademark Office, Word Intellectual Property Organization and the Instituto Nacional da Propriedade Industrial.It was found that the number of patent applications involving Brazilian plants is great. It is necessary to establish biodiversity management plans to ensure national sovereignty in terms of access to genetic resources. Furthermore, conservation programs of flora and endangered species should be prioritized.